Pengaruh Etos Kerja dan Tim Kerja terhadap Kinerja Pegawai pada Satuan Polisi Pamong Praja Kabupaten Tapanuli Tengah - Weandy SK Bangun; Kaharuddin Kaharuddin; Yenni Sofiana Tambunan (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of Work Ethic and Teamwork on Employee Performance at the Civil Service Police Unit (Satpol PP) of Central Tapanuli Regency. This research uses a quantitative descriptive approach to describe and analyze the relationships between variables. The population consists of 370 employees, including 22 civil servants (PNS), 10 contract-based government employees (P3K), and 338 temporary employees (THL). The sample was determined using 15% of the population, resulting in 56 respondents. The data used in this study are primary data collected through questionnaires. The results of the instrument test indicate that all items for the variables of Work Ethic, Teamwork, and Employee Performance are valid and reliable, with Corrected Item-Total Correlation values greater than 0.300 and Cronbach’s Alpha values above 0.600. The classical assumption tests show that the data are normally distributed and free from multicollinearity, heteroscedasticity, and autocorrelation, indicating that the regression model is appropriate. The results of multiple linear regression analysis reveal that Work Ethic and Teamwork have a positive effect on Employee Performance. Partially, both independent variables have a significant effect on performance, as indicated by t-values greater than the t-table and significance values below 0.05. Simultaneously, Work Ethic and Teamwork also have a significant effect on Employee Performance based on the F-test results. Therefore, the hypotheses proposed in this study are accepted.